Fluktuasi Harga dan Integrasi Pasar Cabai Merah Besar (Studi Kasus: Pasar Induk kramat Jati dan Pasar Eceran di DKI Jakarta): Price Fluctuations and Market Integration of Big Red Chilies (Case Study: Kramat Jati Main Market and Retail Market in DKI Jakarta) - Yuditya, Azzahra; Hardjanto, Arini; Sehabudin, Ujang (Indonesian Journal of Agricultural Resource and Environmental Economics, 2023)
Fluktuasi harga pangan merupakan fenomena yang menjadi perhatian yang serius yang dapat memengaruhi tingkat inflasi. Salah satu kelompok sayuran yang menyumbang inflasi adalah cabai merah besar. Penelitian ini bertujuan untuk menganalisis pola perkembangan harga cabai merah besar di Pasar Induk Kramat Jati (PKIJ) dan di lima pasar eceran di DKI Jakarta, faktor –faktor yang memengaruhi flukuasi harga cabai merah besar di PIKJ, peramalan harga cabai merah besar di PIKJ tahun 2023, dan integrasi pasar antara pasar grosir dengan pasar eceran di DKI Jakarta. Metode yang digunakan adalah metode analisis deskriptif, OLS (Ordinary Least Squares), ARIMA (Auto Regressive Integrated Moving Average), and VECM (Vector Error Correction Model) techniques. Hasil penelitian menunjukkan bahwapola perkembangan harga cabai merah besar di PIKJ dan di lima pasar eceran di DKI Jakarta memiliki pola yang berfluktuasi. Hasil peramalan harga rata –rata cabai merah besar di PIKJ selama 8 bulan sebesar Rp29.858/kgsertahasil integrasi pasar menunjukkan bahwa PIKJ memiliki keterkaitan jangka panjang antara Pasar Jatinegara, Pasar Minggu, dan Pasar Tanah Abang. Fluctuations in food prices are a matter of serious concern as they can impact the inflation rate. Among the contributing factors to inflation, a significant group includes certain vegetables, such as large red chilies. This study aims to analyze the patterns of large red chili price developments in Kramat Jati Market (PIKJ) and five retail markets in DKI Jakarta. It also seeks to examine the factors influencing fluctuations in large red chili prices in PIKJ, forecast large red chili prices in PIKJ for 2023, and assess market integration between wholesalers and retail markets in DKI Jakarta. The research employs a descriptive analysis method, as well as OLS (Ordinary Least Squares), ARIMA (AutoRegressive Integrated Moving Average), and VECM (Vector Error Correction Model) techniques. The findings reveal that large red chili prices in PIKJ and five retail markets in DKI Jakarta exhibit a fluctuating pattern. Significant factors affecting large red chili price fluctuations in PIKJ include the average lag of red chili prices in PIKJ, the average price of curly red chilies in PIKJ, and the availability of stock of large red chilies in PIKJ. Meanwhile, the average price forecast for large red chili in PIKJ for the next eight months is 29,858 IDR/kg. The market integration analysis indicates that PIKJ exhibits a long-term relationship with Jatinegara Market, Sunday Market, and Tanah Abang Market